Optimization of the Recycling Process for Aligned Short Carbon Fiber TuFF Composites - Balaga, Uday Kiran; Gunes, Aydin; Ozdemir, Tekin; Blackwell, Chris; Davis, Mark; Sauerbrunn, Steven; Heider, Dirk (MDPI, 2025)
Recycling of carbon fibers enables a sustainable feedstock for industrial applications of high-performance composite materials. This allows light weighting with recycled carbon fibers due to their superior mechanical properties while reducing the high embodied energy and cost of virgin carbon fiber composites. This study optimizes a pyrolysis cycle for fiber recovery of an aerospace-grade thermoset prepreg and a cleaning (oxidation) step to minimize fiber degradation and left-over resin residue, enabling dispersion and alignment of the recycled, discontinuous fibers in the Tailorable Universal Feedstock for Forming alignment process. The study balances the influence of the optimized thermal cycle (pyrolysis + oxidation step) on recycled carbon fiber strength retention with the ability to disperse at the filament level to create aligned, recycled carbon fiber composite samples with high fiber volume fraction. The optimized thermal cycle for efficient fiber recovery applied a pyrolysis step at 500 degrees C for 4 h in an inert gas environment and an additional oxidation step at the same temperature for 100 min. This resulted in similar to 20% strength degradation of the fiber compared to the virgin fiber. The processed recycled composite achieved 44% fiber volume fraction with full modulus translation (similar to 128 GPa) compared to the virgin continuous composite with strength translation (similar to 870 MPa), reaching similar to 50%.
Keywords: Carbon Fiber Recycling; Pyrolysis; Oxidation; Short Fiber Aligned Composites; Tailored Universal Feedstock For Forming (Tuff)